An Inflated Probability Model for the Rural Out-Migration - Rajendra Tiwari, Himanshu Pandey*, (Recent Research in Science and Technology, 2011)
The main objective of the paper is to develop an inflated Probability model for the total number of migrants from a household. The suitability of the model is tested through observed data.